Managing With or Without Unions: A Matter of the Frame of Reference - Onabanjo, Idowu (Archives of Business Research, 2017)
It is possible to manage with or without unions depending on the frame of reference that management embraces. However, there are advantages and disadvantages to whichever frame of reference a management chooses. Managing without unions is like a government without opposition. It is unitary; it is autocratic in its worst, paternalistic at its best. Managing with unions is pluralistic and requires a process of accommodating various stakeholders.